Bioecological Distribution of Aedes Mosquito Density in Coastal and Highland Areas - Fajar Akbar; Zrimurti Mappau; Mulyadi Mulyadi; Erlani Erlani; Fahrul Islam; Ridhayani Adiningsih; Miftah Chairani; Muhammad Rusdi (Public Health of Indonesia, 2026)
Background: Disease transmission is strongly supported by the presence of disease vectors. Along coastal areas, shrimp ponds, swamps, and stagnant water are commonly found, which provide ideal breeding sites for mosquitoes, where many vector-borne diseases are prevalent. Objectives: This study aims to determine the bioecological diversity of virus-carrying mosquitoes in light of the persistently high incidence of dengue hemorrhagic fever (DHF), particularly focusing on the disease vector Aedes spp. The study examines aspects of bioecological distribution, species diversity of mosquitoes in coastal and highland areas, species distribution patterns in both regions, and how these distributions are influenced by geographic location, habitat type or breeding sites, mosquito density, and environmental characteristics of coastal and mountainous regions. Methods: This study employed an observational approach with a bioecological study design. Data were analyzed descriptively to assess egg and larval density of mosquitoes using a free collection method conducted in coastal and highland areas of Mamuju and Polewali Mandar Regencies, specifically in areas reporting DHF cases. Results: The results indicate that ovitraps are effective in reducing Aedes spp. mosquito density, as reflected by the ovitrap index. Conclusion: The ovitrap index was higher in highland areas than in coastal areas, influenced by environmental factors such as temperature, humidity, wind speed, and the abundance of breeding sites. It is expected that the local government, through the District Health Office, will provide community education on controlling Aedes spp. mosquitoes by installing ovitraps in individual households. Keywords: bioecology; Aedes spp.; coastal; highland areas